ANALISIS MEDIA PEMBELAJARAN TV SMART PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS DARUL ULUM - Sari, Qoriah Pulung; Yushinta Eka Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Islamic cultural history is a difficult and difficult subject to master, especially for students. Students feel less interested when they encounter difficult Islamic cultural history questions and even tend to avoid them and teachers can use technology-based learning media, namely smart TV. The purpose of the study was to analyze technology-based learning media (smart TV) in the subject of Islamic cultural history at MTS Darul Ulim Purwogondo. This study uses a descriptive qualitative approach. Data collection through observation analysis, interviews and documentation. The results of the study showed that the success of students in learning was influenced by teachers on how they teach, in addition, adequate facilities and infrastructure will also support success in achieving learning objectives. The way to optimize the achievement of learning objectives is to use the right media. From the use of the right media can affect learning interest, the selection of smart TV media is chosen as an effective learning strategy so that students actively develop knowledge.